Edukasi Risiko Computer Vision Syndrome (CVS) Pada Pegawai Perusahaan Umum Jasa Tirta I Kota Malang - Nikmatur Rosidah; Bayu Prastowo; Nur Halizah Rahma Dini; Syabina Zahra Rienanda; Donny Septian Wibisono (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Long-term exposure to digital screens is a main factor in the incidence of Computer Vision Syndrome (CVS). This phenomenon is due to the rapid use of computers, gadgets, and other electronic devices. This service aims to mapping and educating eye fatigue, irritation, dry eyes, and visual impairment as symptoms of Computer Vision Syndrome (CVS). This community service uses the Participatory Approach method on 60 participants at the Public Company Jasa Tirta I, Malang City. This service has been permitted through No.0007/UM/VP SDK/VII/2024. Education is carried out using Dale's Cone of Experience theory with a combination of lectures and stimulation. Participants generally experienced myopia refractive error. In addition, there was an increase in participant knowledge reaching 60.42%. These findings confirm that a service-based educational approach can be an effective method in addressing digital health issues